2020
DOI: 10.1038/s41467-019-13850-7
|View full text |Cite
|
Sign up to set email alerts
|

Prox1-positive cells monitor and sustain the murine intestinal epithelial cholinergic niche

Abstract: The enteric neurotransmitter acetylcholine governs important intestinal epithelial secretory and immune functions through its actions on epithelial muscarinic Gq-coupled receptors such as M3R. Its role in the regulation of intestinal stem cell function and differentiation, however, has not been clarified. Here, we find that nonselective muscarinic receptor antagonism in mice as well as epithelial-specific ablation of M3R induces a selective expansion of DCLK1positive tuft cells, suggesting a model of feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 67 publications
3
65
0
Order By: Relevance
“…Therefore, the distribution of tuft cells in human lung still needs to be carefully investigated. The knockout of Pou2f3 gene indicates the specific deletion of tuft cells and Pou2f3 –/– mice exhibit impaired mucosal type 2 responses and epithelial regeneration ( Gerbe et al, 2016 ; Middelhoff et al, 2020 ). In this respect, the long term targeting on IL17RB to monitor tuft cell-like human colorectal cancer still needs further research to avoid the potential damage to the homeostasis of colorectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the distribution of tuft cells in human lung still needs to be carefully investigated. The knockout of Pou2f3 gene indicates the specific deletion of tuft cells and Pou2f3 –/– mice exhibit impaired mucosal type 2 responses and epithelial regeneration ( Gerbe et al, 2016 ; Middelhoff et al, 2020 ). In this respect, the long term targeting on IL17RB to monitor tuft cell-like human colorectal cancer still needs further research to avoid the potential damage to the homeostasis of colorectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Using electron microscopy, researchers have made it clear that the expressions of ChAT in mice localize in the cytosol as well as the nucleus ( Kummer and Krasteva-Christ, 2014 ; Friedman et al, 2019 ). A recent study in intestinal epithelium has demonstrated that increased ChAT expression is related to the expansion of tuft cells following the increase of ACh secretion ( Middelhoff et al, 2020 ).…”
Section: Acetylcholine Biosynthesis and Release In Tuft Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the close interaction between airway tuft cells and cholinergic neurons has been previously demonstrated ( 37 ), with recent demonstrations of tuft cell acetylcholine driving ciliary beating in a Trpm5-dependent fashion ( 38 ), their role in cholinergic neuron signaling in the intestine is less clear. There is evidence that during genetic and antagonist muscarinic receptor blockade, small intestinal tuft cells arise with an enteroendocrine-like phenotype to sustain the murine intestinal epithelial cholinergic niche ( 39 ). Moreover, as acetylcholine receptors are also expressed on diverse cell types, including goblet cells (where acetylcholine promotes mucus secretion), dendritic cells, macrophages, as well as B and T cells ( 40 , 41 ), there is the unexplored possibility that tuft cells may also play a larger role in anthelmintic immunity via their production of acetylcholine.…”
Section: Current Tuft Cell Advancementsmentioning
confidence: 99%